Prolongation of a pregnancy with second trimester severe oligohydramnios to term: a case report - Bapat, Alka C.; Paidhungat, Nitin P (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The occurrence of oligohydramnios complicating a pregnancy is seen in 0.8 to 5.5 % of pregnancies. Severe Oligohydramnios, though not clearly defined, but clinically with an AFI of less than 5 cm appears to be an important predictor for an abnormal fetal outcome. In general, the prognosis of mid trimester oligohydramnios is still poor. Hence we report a case with a very favourable neonatal outcome following severe oligohydramnios documented in early pregnancy. The aim of this case report is to add our experience to the currently limited literature regarding the best treatment of this unique obstetrical problem.